Efektivitas Poster Kampanye Sosial Safety Riding dari Limbah Kain Batik untuk Mengubah Perilaku Mahasiswa Universitas Muhammadiyah Cirebon dalam Berkendara - Teddy Dyatmika; Dikhorir Afnan (An-Nida : Jurnal Komunikasi Islam, 2018)
The present study intends to investigate the changing of students’ behavior during driving. The changing is influenced by the implementation of social campaign of safety riding by utilizing waste batik cloth material in Muhammadiyah University of Cirebon. This study applies posters, as the media, concerning social campaign of safety riding made of waste batik cloth material in Cirebon. Nineteen students from entire study program in Muhammadiyah University of Cirebon are chosen as the objects/participants in this study. This study employs a quantitative study. The data are obtained through an instrument namely closed questionnaires. The result of the study indicates that there is a difference attitude among students after the social campaign of safety riding utilizing waste batik cloth material is implemented with the statistical score 5, 09537.